O cineasta errante : caminhos e encontros na realização de um filme de um homem só - Spolidoro, Gustavo (2013)
This thesis and it companion film aim to understand one-man filmmaking, from the origins of cinema to the present day. The idea for this thesis and the feature film Errante um filme de encontros ( Wandering - a film about encounters ) first came to me in 2006, during a session of The Gleaners and I from Agnès Varda, presented by Jean-Claude Bernardet. The empiric experience of making a film with a crew of one person only is joined by a theoretical analysis based in works from authors as Guy Gauthier, Andrei Tarkovski, Arlindo Machado and Antonio Weinrichter, and films as the already mentioned The Gleaners and I , Nanook of the North , I, a Negro and Sans Soleil . In a time when everyone has a camera in their pocket, it becomes key to understand the artist s role in filmmaking and the expression of their subjectivity. The making of a one man film is within reach of all that have access to equipment, but mainly of those with the intention to make it in such a way.